A review of the quality of care following prolonged seizures in 1–18 year olds with epilepsies. (January 2015) - Hunter, Lindsey; Sidebotham, Peter; Appleton, Richard; Dunkley, Colin
Highlights: There have been improvements in epilepsy care compared with other studies. Importance of clear communication with carers, including detailed emergency care plans. Buccal midazolam should be the rescue medication of choice for ambulance crews. Appropriate training of buccal midazolam should be provided. Admission to intensive or high-dependency care provides opportunity for review of a child's care. Abstract: Purpose: To review the quality of care of children and young people with epilepsies who, following a prolonged seizure, received high-dependency or intensive care. To identify and learn from clinical, organisational, management or personal issues that contributed to these admissions, in order to inform practice and improve clinical services for children across the UK. Method: Notifications were collected from consultant paediatricians in England, Wales, Scotland and Northern Ireland over a 10-month period. For all eligible cases a clinical questionnaire was sent to the notifying clinician. A sample of these cases were selected for a detailed case note review. Case notes were reviewed by paediatrician–nurse pairs using a purpose-built assessment tool derived from national guidelines. Results: Data were collected from 135 clinical questionnaires, and 36 sets of case notes were reviewed. Findings were compared to national standards of care and emerging themes identified. There was evidence of good epilepsy management in many cases. In some cases there was evidence of a lack of clear emergency care plans, of delays in administration of emergency medication, and of deviation from established national guidelines. Conclusion: The findings of this review suggest there have been improvements in the care of children and young people with epilepsies presenting with prolonged seizures compared to previous studies. Nevertheless, further improvements are needed, particularly in communication with families and prompt administration of emergency medication.